Large-area flat-panel detector versus conventional detector for full-spine digital radiography: a retrospective comparative study - Fuqiang Lin; Yuting Gao; Wei Deng; Hong Ren (Frontiers in Medicine, 2026)
Objective To compare workflow efficiency, tube current-exposure time product (mAs), and image quality between a DRX-LC large-area flat-panel detector and a conventional flat-panel detector for full-spine digital radiography. Methods In this retrospective comparative study, radiographs and examination records of 90 adult patients who underwent full-spine anteroposterior (AP) and lateral (LAT) digital radiography between August and September 2025 were retrospectively reviewed. Patients were categorized according to the detector used during clinical imaging into a DRX group (Carestream DRX-LC, 42.58 × 120.87 cm) or a conventional group (33.0 × 43.2 cm), with 45 patients in each group. The DRX group underwent single-exposure full-spine imaging, whereas the conventional group underwent 4–6 segmented acquisitions followed by automatic stitching. Examination duration and mAs values for AP and LAT imaging were recorded. Image quality was independently assessed by four experienced reviewers using a 4-point scoring system, and mean scores were analyzed. Results Baseline characteristics were comparable between the two groups (all P > 0.05). The DRX group had a significantly shorter examination duration than the conventional group (3.63 ± 0.83 min vs. 11.59 ± 2.31 min, P < 0.001). Subjective image quality scores were significantly higher in the DRX group [median [IQR], 4 [3–4] vs. 3 [2.5–3]; P < 0.001]. Compared with the conventional group, the DRX group also showed lower AP mAs (39.12 ± 1.16 vs. 70.43 ± 10.45, P < 0.001), lower LAT mAs (54.56 ± 3.02 vs. 76.69 ± 12.83, P < 0.001), and lower cumulative mAs (93.88 ± 3.59 vs. 146.89 ± 21.82, P < 0.001). The single-exposure DRX-LC images showed clearer visualization of vertebral cortices and trabeculae and fewer artifacts. Conclusion For full-spine digital radiography, use of the DRX-LC large-area detector was associated with fewer exposures, shorter examination time, lower mAs requirements, and better subjective image quality. These findings support its clinical value for optimizing full-spine imaging workflows.